EU joint programming: lessons from South Sudan for EU aid coordination - Mark Furness; Frank Vollmer (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Joint programming (JP) is the latest effort to improve the coordination of EU and member state development policy at headquarters level, and to better streamline aid delivery at the country level. JP aims to improve the effective and efficient delivery of European aid by reducing fragmentation among EU donor aid programmes and projects. At the same time, the EU promises to increase partner country ownership by basing its JP documents on national development strategies. Momentum and interest have picked up: the European External Action Service (EEAS) and the Commission's DG DevCo are pushing for wider use of joint programming under the 2014-2020 EU Budget. The preparation of joint country strategies is currently at various stages for around 20 countries where the EEAS and DevCo plan to have JP operational by the end of 2014. There may be as many as 50 JP exercises underway by 2020 (see Table 1). Although joint programming is an EU exercise, non-EU donors such as the United States, Norway, Japan, the World Bank or UNDP, are welcome to join and several have expressed interest in taking part on a case-by-case basis. From the partner-country perspective, JP offers to reduce the burden of having to deal with several EU actors and agencies. The JP exercise was piloted in two of the world's most fragile countries, Haiti and South Sudan. Theoretically, South Sudan offered promising conditions for JP: although the world's newest country was hardly a 'blank canvas' following independence from Khartoum in July 2011, most donors were recent arrivals. Synchronisation and fragmentation problems were not as acute as in countries where larger numbers of donors with established programmes stymie coordination efforts. An EU Single Country Strategy paper, aligned with South Sudan's 2011-2013 Development Plan, was published in January 2012. Its implementation cannot be considered an unqualified success. While South Sudan's extreme political, economic and security challenges impacted on the JP exercise, the experience also has implications for JP in other settings. As JP is applied in more countries, the South Sudan experience suggests three priorities for future exercises: Be flexible: Circumstances can change quickly, especially in fragile states. Programmes that cannot adapt and demonstrate added value at the country level risk losing legitimacy. Ensure commitment: Member state buy-in is essential if JP is to go beyond a strategy paper. While EU member states have formally committed to the JP framework, this does not mean that they love it. Steps to synchronise project cycles could be a first indicator of greater commitment. Programmes backed by joint financing and implementation are likely to be more robust. JP is no magic bullet: There are limits to what the EU can achieve on its own. The partner country government's political will to make JP work for them, and the capacity of their systems, are key variables.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Wirksamkeit und Evaluierung